Green approach in road construction / Suhaila Ali ... et al.] - Suhaila Ali, Ali; Nurul Fatihah, Yahaya; Norbaizura, Abu Bakar; Mohd Hafiz, Saberi; Norhafizah, Yusop; Farhan, Md Dahlan (2015)
Formation of road network involves various construction activities which may include deforestation that gives impact to the environment. Therefore road construction has indirectly affected the environment in countless ways and also has increased the destruction of the natural environment. As the environmental impacts of road construction activities become more apparent, green approach in road construction moves forward and gaining its momentum. A green approach can be defined as a process of planning, design and constructing using technology and concept at low cost in minimizing environmental impacts on communities and natural habitat. However, in the current road project, green approach is still new and sometimes contractors do not take this matter seriously. In this paper, the readiness and acceptability of contractors towards a green approach in road construction is studied. The data for this study was obtained through a set of questionnaire to targeted respondent and was analyzed by using SPSS software. From the study, it was found that green approach in road construction is being accepted and widely understood by a majority of main players in the construction industry but the implementation of the green approach has been found to be not widely carried out. From the analysis that has been carried out, the result reveals that the government should come out with the strategies to improve the implementation of green approach.